Difference or ratio: Implication of status preference on stagnation - Yoshiyasu Ono; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2012)
We consider a dynamic macroeconomic model with households that regard relative affluence as social status. The measure of relative affluence can be the ratio to, or the difference from, the social average. The two specifications lead to quite different results: with the ratio specification full employment is necessarily realized, whereas with the difference specification persistent shortages of aggregate demand and employment can arise. Furthermore, using the data of an experiment of affluence comparison we empirically find that the difference specification is far more persuasive than the ratio specification. Thus, the present model provides an analytical framework for persistent stagnation.
Keywords: C91; E12; E24; 330; status; stagnation; unemployment; Sozialer Status; Erwerbstätigkeit; Diskrete Entscheidung; Test; Japan